Following Teaching of Psychology Into Middle Age: Changes, Contributors, and Contents. (January 2013) - Griggs, Richard A.; Collisson, Brian
Honoring Teaching of Psychology ( ToP ) as it approaches its 40th anniversary, we extend prior overviews of its development and growth into 2012. We describe changes in editorial staff and journal organization, identify and describe the top 20 most frequent contributors to ToP, and present the results of a content analysis of issues published from 1999 through mid-2012 to complement past content analyses. We conclude that as ToP enters middle age, it has professionally matured throughout adulthood to have a fruitful life as a topical journal and has outgrown its earlier newsletter trappings with essentially all of its journal space now devoted to articles on teaching for teachers.